(untitled) (Baghdad Science Journal, 2013)
Some physical properties enthalpy (?H), entropy (?s), free energy (?G),capacities(?cp?) and Pka values) for valine in dimethyl foramideover the temperature range 293.15-318.15K, were determined by direct conductance measurements. The acid dissociation at six temperature was examined at solvent composition x2) involving 0.141 of dimethyl foramide . As results, calculated values have been used to determine the dissociation constant and the associated thermodynamic function for the valine in the solvent mixture over temperatures in the range 293.15-318.15 k. The Pka1, and Pka2 were increased with increasing temperature.